Triforis isleana Velain 1877 ... - Bakker, Piet A. J.; Albano, Paolo G. (Zenodo, 2022)
Triforis isleana Vélain, 1877 Triforis isleanus Vélain, 1877: 112, pl. 3, fig. 10. Type locality. St. Paul and Amsterdam Island. Type material. MNHN-IM-2000-1103, holotype. Distrubition. Philippines (Hidalgo 1905), St. Paul and Amsterdam Island (Vélain 1877; Tryon 1887; Paetel 1888). Remarks. The genus Triforis is of feminine gender, therefore the name should be Triforis isleana. ... : Published as part of Bakker, Piet A. J. & Albano, Paolo G., 2022, Nomenclator, geographic and stratigraphic distribution of the family Triphoridae (Mollusca: Gastropoda), pp. 1-216 in Zootaxa 5088 (1) on page 96, DOI: 10.11646/zootaxa.5088.1.1, http://zenodo.org/record/5836536 ...